THE DIASPORA AND ECONOMIC DEVELOPMENT IN AFRICA - (:unkn) unknown (My University, 2018)
While the dominant collective belief asserts that brain drain is detrimental to the development of small economies, new studies hold the reverse view. This paper aims at studying the role of the African Diaspora in the economic development of Africa. It analyzes both the overall effect and the specific effect of emigration according to the level of education of emigrants. Then, through a deeper investigation, the paper analyzes the main channels through which the Diaspora influences economic development in Africa. The results show that the African Diaspora contributes positively, significantly and robustly to the improvement of real per capita income in Africa. These findings challenge the dominant collective belief since the higher the educational level of the emigrants, the greater the impact of the Diaspora on the level of economic development. Improvements in human capital, total factor productivity and democracy are effective transmission channels of this impact. Finally, the results show that while high-skilled emigrants have an overall greater impact on economic development and democracy, those with a low level of education contribute more to remittances to Africa. The establishment of an annual African Diaspora Summer School (ADSS) by the AfDB in partnership relevant international and regional stakeholders as a channel for the transfer of knowledge, technology and experience would further strengthen the role of the Diaspora in Africa’s economic development.
Keywords: African Research